Medical informatics education - past, today and future - Masic, Izet; Pandza, Haris (European Journal for Biomedical Informatics, 2018)
The development of medical informatics goes back to the second half of the twentieth century with the start of the automation of processes. Medical informatics education plays an important role in the education of health care providers and medical providers. Education in medical informatics is not only important for medical students but also for other medical staff at all professional levels of education. Integrating medical Informatics into the full spectrum of medical education is a vital step required for the understanding and practice of modern medicine. There are curricula in the field of medical informatics at many universities in Europe. Great roles in this field had the International Medical Informatics Association (IMIA) and – the European Federation for Medical Informatics (EFMI). Working groups of IMIA and EFMI defined and recommended concepts and methodologies of education for medical informatics on three levels. Generally in all European countries medical education at universities is organized on the basis of the Bologna concept, which has improved the quality of teaching process in plenty matters, but it has brought a big number of highly educated staff, that are younger than average, but also have average level of knowledge. Basically, the Bologna system has brought averageness we tried to escape from. With the introduction of the Bologna process in Bosnia and Herzegovina and other countries, a new process is being introduced which introduces a new curriculum, a greater number of subjects, a complemented systematization of knowledge and the need to correct past attitudes. Since the curriculum of medical informatics varies between countries and universities and faculties in the country, it is necessary to take steps towards the unification of the curriculum at the international level. Aim of the article is to show the status of medical informatics education in Bosnia and Herzegovina and Europe.
Keywords: Curriculum; Bosnia and Herzegovina; Medical Informatics; Boloňský proces; kurikulum; Education, Distance; Bosna a Hercegovina; distanční studium; Education, Professional; lékařská informatika; Universities; vzdělávání odborné; univerzity